The challenges of gamifying CSR communication - Maltseva, Kateryna and Fieseler, Christian and Trittin-Ulbrich, Hannah (Corporate Communications: An International Journal, 2019)
Purpose A growing number of research report positive effects of gamification, that is the introduction of game elements to non-game contexts, on stakeholder intentions and behaviors. Hence, gamification is proposed as an effective tool for organizations to educate their stakeholders about corporate social responsibility (CSR) and sustainability-related topics. The paper aims to discuss these issues. Design/methodology/approach In this paper, the authors ask whether gamification can communicate matters of social and environmental concern. Based on three consecutive experimental studies, the authors show that there are boundary conditions to the effectiveness of gamified communication on stakeholder attitude, intention and behavior. Findings The authors find positive, negative and insignificant effects of gamification on pro-environmental attitude, intention and behavior. Based on these ambiguous results, the authors conclude with a call for more rigorous forms of designing gamified experiences to foster stakeholder learning and highlight and develop several such future research and engagement opportunities. Originality/value The study is the first to apply gamification to the context of corporate and in particular CSR communication. It is furthermore one of the first studies that actually research the effects of gamification empirically, and in controlled experimental conditions.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTEwOC9jY2lqLTA5LTIwMTgtMDA5Mg